Optimization of pellet impact drilling regimes by regulation of spacing between a drill bit and a hole bottom - Viktor Viktorovich Urnish; Lev Alekseevich Saruev; Aleksey Lvovich Saruev (Известия Томского политехнического университета: Инжиниринг георесурсов, 2018)
The relevance of the research. One of the main technological parameters of the pellet impact drilling is the spacing between a drill bitand a holebottom. There are several methods and constructions of drill bits that allow keeping this distance with bit feet. In this case, the jet apparatus is held at a certain distance from the blades, which destroy the border zone or central part of the rock by a rotary method. However, no method makes it possible to determine the optimal distance precisely. Since it is quite difficult to calculate the necessary distance for different rocks considering their mechanical characteristics it is very important to identify and keep the optimum spacing between the drill bit and the hole bottom continuously when drilling. The main aim was to analyze the main methods and constructions of keeping the spacing between the drill bit and the hole bottom, also to formulate the requirements. Considering the requirements, to propose a method for keeping the spacing which allows us to determine continuously the necessary distance for current conditions. Object of researches is a bottomhole drilling. Methods: compilation and analysis of the sources; research of technological processes of pellet impact drilling; investigation of the influence of the spacing between the drill bit and the hole bottom on the rock breaking efficiency; representation of a string of drill pipes as an acoustic communication channel in which elastic vibrations spread during impacts of the bounced balls; development of a technological scheme for increasing pellet impact drilling efficiency; experimental studies using an acoustic oscillation sensor and an oscilloscope; analysis of the waveform. Results. The authors have studied the spacing between the drill bit and the hole bottom which affects the efficiency of pellet impact drilling and analyzed the basic methods and constructions. Based on the analysis the requirements were stated. Taking into account the developed requirements the authors proposed the method for keeping the optimal spacing. The paper introduces the experimental results with the proposed method. The results prove the effectiveness of using the method for determining continuously spacing between the drill bit and the hole bottom. The results obtained can be used to select and maintain optimal operating parameters.